2016
DOI: 10.6002/ect.2014.0154
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Focal segmental glomerulosclerosis is a common cause of end-stage renal disease in children. Focal segmental glomerulosclerosis recurrence in renal transplants is a challenging disease, and can cause graft dysfunction and loss. Different therapies exist with varying responses, from complete remission to resistance to all modes of treatment. Abatacept was recently introduced as a treatment for primary focal segmental glomerulosclerosis in native kidneys and in recurrent disease after transplant. We present a pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Garin et al [105] Abatacept (1 or [106] Abatacept (3 doses; 10 mg/kg) 1 patient (< 18 yr) No response Grellier et al [107] Belatacept (days 1, 15, 30 and monthly thereafter, 5 mg/kg) had achieved sustained remission. In a second series, remission was induced in 13/16 patients (81%), which also included PE sessions for 4 of the cases; CyA doses were from 6 to 25 mg/kg per day [46] .…”
Section: Patients (≥ 18 Yr) No Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Garin et al [105] Abatacept (1 or [106] Abatacept (3 doses; 10 mg/kg) 1 patient (< 18 yr) No response Grellier et al [107] Belatacept (days 1, 15, 30 and monthly thereafter, 5 mg/kg) had achieved sustained remission. In a second series, remission was induced in 13/16 patients (81%), which also included PE sessions for 4 of the cases; CyA doses were from 6 to 25 mg/kg per day [46] .…”
Section: Patients (≥ 18 Yr) No Responsementioning
confidence: 99%
“…Nevertheless, other studies of patients with FSGS recurrence have shown a slight/absent response after treatment with CTLA4-Ig [104][105][106][107] , despite the fact that in some of these cases belatacept (able to bind B71 with an higher affinity than abatacept) was adopted.…”
Section: Abataceptmentioning
confidence: 99%
“…A case report recorded a complete remission using the T-cell costimulatory protein B7-1 blocker abatacept, which was not confirmed by others[ 145 - 147 ].…”
Section: Treatment Of Recurrent Fsgsmentioning
confidence: 74%
“…Some evidence and case reports highlighted that abatacept may block the progression of FSGS [44]. In this study, Abatacept induced partial or complete remission of proteinuria in a group of five patients B7-1-positive at glomerular level, suggesting that B7-1 may be a useful biomarker for the treatment of some glomerulopathies.…”
Section: Abataceptmentioning
confidence: 86%